Pain drawing assesment for low back pain - KOJIMA, Hiroshi (The Journal of Japanese Society of Lumber Spine Disorders, 1999)
While great advances have been made in utilizing imaging technology in the diagnosis of low back pain disorders, there are still many patients who present with low back pain for whom a correct diagnosis has not been established. Since late in 1997 we have used Moony and Robertson's Pain Drawing System on patients to verify MRI findings. All patient are required to complete a pain drawing on their first visit to our clinic .The drawing can be done and assessed quickly. The clinician use the scoring sheet drawn up by Wiltse. Our analysis comparing both diagnostic techniques shows a remarkable degree of consistency in our evaluation of low back pain disorder. Utilizing either or both diagnostic methodologies should yield effective evaluations of various low back pain disorders.